2007
DOI: 10.1007/s11067-007-9034-7
|View full text |Cite
|
Sign up to set email alerts
|

R&D for Quality Improvement and Network Externalities

Abstract: We investigate the bearings of network externalities on product quality improvements requiring costly R&D investments. The model considers the dynamic behaviour of a monopolist alternatively maximising profits or social welfare. On the one hand, we confirm much of the acquired wisdom from the static literature on the same topic, about the arising of quality undersupply at the private optimum. On the other, we identify the initial conditions that must be met for R&D activity to be observed under profit-seeking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…When the retailers' ESS is a mixture strategy, NE has a positive impact on product quality‐improvement. These conclusions are different from the findings of Lambertini and Orsini (2010). They found that the increase in NE always leads to a decrease in product quality.…”
Section: Discussioncontrasting
confidence: 99%
“…When the retailers' ESS is a mixture strategy, NE has a positive impact on product quality‐improvement. These conclusions are different from the findings of Lambertini and Orsini (2010). They found that the increase in NE always leads to a decrease in product quality.…”
Section: Discussioncontrasting
confidence: 99%
“…This paper builds the fuzzy comprehensive evaluation of teaching [3], Evaluation factor set, Eq. 1.1…”
Section: Teaching Evaluation Fuzzy Modelingmentioning
confidence: 99%